Soil Water Erosion - Centeri, Csaba (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The purpose of this book is to provide novel results related to soil water erosion that could help landowners and land-users, farmers, politicians, and other representatives of our global society to protect and, if possible, improve the quality and quantity of our precious soil resources. Published papers on the topics are related to new ways of mapping, maps with more detailed input data, maps about areas that have never been mapped before, sediment yield estimations, modelling sheets and gully erosion, USLE models, RUSLE models, dams which stop sediment runoff, sediment influx, solute transport, soil detachment capacities, badland morphology, freeze-thaw cycles, armed conflicts, use of rainfall simulators, rainfall erosivity, soil erodibility, etc.